2022
DOI: 10.3389/fonc.2022.815900
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Bound Paclitaxel: Worthy of Further Study in Sarcomas

Abstract: Taxanes (paclitaxel and docetaxel) play an important role in the treatment of advanced sarcomas. Albumin-bound paclitaxel (nab-paclitaxel) is a new kind of taxane and has many advantages compared with paclitaxel and docetaxel. Nab-paclitaxel is currently approved for the treatment of advanced breast, non-small cell lung, and pancreatic cancers. However, the efficacy of nab-paclitaxel in sarcomas has not been reviewed. In this review, we first compare the similarities and differences among nab-paclitaxel, pacli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 131 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…Some drugs are suitable for combination with PD1/L1 inhibitor, while others are not. For example, it has been demonstrated that the use of glucocorticoids while immunotherapy will lead to poor prognosis ( 90 ). Therefore, chemotherapy drugs that need to be accompanied by glucocorticoids may not be suitable for combination with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some drugs are suitable for combination with PD1/L1 inhibitor, while others are not. For example, it has been demonstrated that the use of glucocorticoids while immunotherapy will lead to poor prognosis ( 90 ). Therefore, chemotherapy drugs that need to be accompanied by glucocorticoids may not be suitable for combination with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel, docetaxel, and cabazitaxel are among the most widely used anticancer drugs for first-line treatments of several solid tumors [ 11 , 12 ]. The incidence of CIPN due to taxane varies from 11% to 87% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later advances in nanotechnology led to the development of nab-paclitaxel (Abraxane ® ), a nanoparticle albumin-bound paclitaxel, which is a new type of taxane antineoplastic drug and has been indicated for the treatment of metastatic breast cancer, non-small cell lung cancer and metastatic pancreatic cancer 201 . Evidence shows that nab-paclitaxel has promising effects in the treatment of angiosarcoma, epithelioid sarcoma, leiomyosarcoma, and other subtypes of soft tissue sarcomas 202 and can be safely combined with gemcitabine or receptor tyrosine inhibitors for an improved curative effect 203 , 204 . On the other hand, nanomedicine-immunotherapy combinations remain poorly investigated in sarcomas.…”
Section: Strategies To Overcome Barriers To Sarcoma Immunotherapymentioning
confidence: 99%